Trybunał Konstytucyjny jako organ stojący na straży konstytucyjności. Uwagi na tle analizy orzecznictwa z 2017 r. - Tkacz, Sławomir (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2018)
The Constitutional Tribunal`s task is to examine the constitutionality of legal acts. The dispute over the Tribunal in Poland in 2016–2017 raises the question whether it still performs this function. The author addresses this issue in the light of the analysis of judgments issued by the Constitutional Tribunal in 2017. In conclusion, the Author indicates that due to the nature of the activities, the constitutional court will always be included in the political discourse in some extent. The answer to the question whether the Polish Constitutional Tribunal constitutes a barrier for the legislator’s actions depends in a large extent on the legislator himself. The latest defines the normative conditions of his activity as well as decides on the selection of the Tribunal`s judges. The study closes the remarks regarding the constitutional judiciary model in Poland in the future.
The Constitutional Tribunal as an authority safeguarding constitutionality. Comments against the analysis of the case law of 2017
Keywords: Constitutional Tribunal; constitutional crisis; separation of powers; rule of law; constitutional interpretation